Effect of extruded linseeds alone or in combination with fish oil on intake, milk production, plasma metabolite concentrations and milk fatty acid composition in lactating goats. (10th December 2014) - Bernard, L.; Leroux, C.; Rouel, J.; Delavaud, C.; Shingfield, K. J.; Chilliard, Y.
Abstract : Based on the potential benefits for long-term human health, there is interest in developing sustainable nutritional strategies for lowering medium-chain saturated fatty acids (FA) and increasing specific unsaturated FA in ruminant milk. Dietary supplements of extruded linseeds (EL), fish oil (FO) or a mixture of EL and FO increase cis -9, trans -11 CLA and long-chain n-3 polyunsaturated FA in bovine milk. Supplements of FO cause milk fat depression in lactating cows, but information for dairy goats is limited. A total of 14 Alpine goats were used in a replicated 3×3 Latin square with 28-days experimental periods to examine the effects of EL alone or in combination with FO on animal performance, milk fat synthesis and milk FA composition. Treatments comprised diets based on natural grassland hay supplemented with no additional oil (control), 530 of EL or 340 g/day of EL and 39 g/day of FO (ELFO). Compared with the control, ELFO tended ( P =0.08) to lower milk fat yield, whereas EL increased ( P <0.01) milk fat content and yield (15% and 10%, respectively). Relative to EL, ELFO decreased ( P <0.01) milk fat content and yield (19% and 17%, respectively). Relative to the control and ELFO, EL decreased ( P <0.05) milk 10:0 to 16:0 and odd- and branched-chain FA content and increased 18:0, cis -18:1, trans -13 18:1 (and their corresponding ∆-9 (desaturase products), trans -12, cis -14 CLA, cis -13, trans -15 CLA, cis -12, trans -14 CLA and trans -11, cis -13 CLA and 18:3n-3 concentrations. ELFO was more effective for enriching ( P <0.05) milk cis -9, trans -11 CLA and trans -11 18:1 concentrations (up to 5.4- and 7.1-fold compared with the control) than EL (up to 1.7- and 2.5-fold increases). Furthermore, ELFO resulted in a substantial increase in milk trans -10 18:1 concentration (5.4% total FA), with considerable variation between individual animals. Relative to the control and EL, milk fat responses to ELFO were characterized by increases ( P <0.05) in milk trans -16:1 (Δ9 to 11), trans -18:1 (Δ6 to 11), trans -18:2, CLA ( cis -9, trans -11, trans -9, cis -11, trans -8, trans -10 and trans -7, trans -9) and 20- and 22-carbon FA concentrations. Overall, EL resulted in a relatively high cis -9 18:1 concentration and an increase in the 18:3n-3/18:2n-6 ratio, whereas combining EL and FO resulted in substantial increases in trans -FA, marginal enrichment in 20:5n-3 and 22:6n-3 and lower 16:0 concentration changes associated with a decrease in milk fat content. In conclusion, data provide further evidence of differential mammary lipogenic responses to diet in the goat compared with the cow and sheep.